The Past in Public Space.: “Der Jahrhundertschritt”: A Lieu de Memoire As An Urban Intervention of Memory - Pank, Julia Friederike (Street Art & Urban Creativity, 2020)
Sites of memories do not always take the form of a memorial or museum – objects placed in the midst of the urban space, like the sculpture “Der Jahrhunderschritt” in a shopping street of Leipzig, Germany, serve just as well (or better) to trigger the memory of past events and relate them by direct encounter to the immediate present. In what ways do encounters with the sculpture serve as a stepping stone for a memory culture which confronts and interrupts the stream of passersby? How does it relate to its surroundings, what are the reactions with which the artwork is met? This article explores the potential of this specific lieu de memoire conceptualized as an urban intervention in bringing the past to the present, analyzing how awareness for the past-present-future continuum is raised in the mundane, yet historically delicate context of Leipzig’s inner city as a shopping street that used to be the site of the Peaceful Revolution of 1989.